2006
DOI: 10.1080/14693062.2006.9685583
|View full text |Cite
|
Sign up to set email alerts
|

From inadvertent to reluctant pioneer? Climate strategies and policy style in France

Abstract: To comply with the Kyoto Protocol, signatory nations have implemented a policy template of reducing greenhouse gas emissions mainly from the electricity generation and heavy industry sectors. This article shows how, in the case of France, a policy style based on 'environmental meso-corporatism' has largely exhausted this 'standard recipe'. To consider how far France has developed fresh solutions, two phases of climate policy-making in the 2000s are analysed. Increased recourse to new environmental policy instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A classic example of dirigisme are the 'grand projets'nuclear power, the TGV, aviationof the 1970s and 1980s. At the same time, French policymaking is characterised by more consensual sectoral styles, embedded in meso-corporatist regimes (Szarka, 2006). Szarka (2004), drawing on Muller and Saez (1985), distinguishes three characteristics of this 'corporatisme à la française': (i) sectoral interest representation, monopolised by a single lobby; (ii) close relationships between parts of the administration and sectoral interests; and (iii) the capacity to exclude other, non-economic interests and governmental actors.…”
Section: Archetypementioning
confidence: 99%
See 1 more Smart Citation
“…A classic example of dirigisme are the 'grand projets'nuclear power, the TGV, aviationof the 1970s and 1980s. At the same time, French policymaking is characterised by more consensual sectoral styles, embedded in meso-corporatist regimes (Szarka, 2006). Szarka (2004), drawing on Muller and Saez (1985), distinguishes three characteristics of this 'corporatisme à la française': (i) sectoral interest representation, monopolised by a single lobby; (ii) close relationships between parts of the administration and sectoral interests; and (iii) the capacity to exclude other, non-economic interests and governmental actors.…”
Section: Archetypementioning
confidence: 99%
“…Szarka (2004), drawing on Muller and Saez (1985), distinguishes three characteristics of this 'corporatisme à la française': (i) sectoral interest representation, monopolised by a single lobby; (ii) close relationships between parts of the administration and sectoral interests; and (iii) the capacity to exclude other, non-economic interests and governmental actors. These features have been well-documented for agricultural and environmental policy sectors, whereby it has been suggested that technical, supply-side solutions are favoured over social innovations, such as changes of consumption practices (Szarka, 2006). Although it is sometimes suggested that the French modus operandi has shifted towards a more consensual style, this seems more a change of emphasis than a radical departure from the past (cf.…”
Section: Archetypementioning
confidence: 99%
“…Following the Rapport Cochet, FIT were introduced in the early 2000s. Conflicts with EdF over tariff levels were managed paternalistically, as the government pressured EdF to consent (Szarka 2006). In addition to feedin tariffs, regulation on tender procedures was updated, thus creating two parallel support schemes: FIT for small-scale generation and tenders for large-scale generation.…”
Section: Setting the Stagementioning
confidence: 99%
“…220-221;Whiteside et al 2010, p. 453). At first glance, this might suggest a shift to a more consensual approach, but the format did not allow participants to shape the agenda or to influence final decisions, which was experienced as particularly frustrating by those in favour of transformation-given the unchallengeable position of nuclear, renewable energy proponents still felt marginalised (Szarka 2006;Brand-Schock 2010). Even though there were attempts to provide new modes of societal/public involvement, French energy policy reflected an étatist-paternalistic stance.…”
Section: Setting the Stagementioning
confidence: 99%
“…However, argument on this counterfactual basis leads to relatively low emission avoidance factors of 200-250 g CO 2 /kWh (Bataille and Birraux, 2006, p135). The residential and transport sectors -which have seen strong growth in emissions in recent years -offer far more scope than this for emissions reductions (Szarka, 2006). Thus, climate protection considerations have not provided a strong mobilizing discourse for wind power deployment in France.…”
Section: Reductions Of Greenhouse Gas Emissionsmentioning
confidence: 99%